Reaction Calorimetry for Exothermic Reactions in Plate‐Type Microreactors Using Seebeck Elements1. Issue 11 (9th October 2017) - Reichmann, Felix; Millhoff, Stefan; Jirmann, Yannick; Kockmann, Norbert
Abstract: A flexible reactor and measurement setup to safely obtain thermokinetic data for exothermic chemical reactions in plate‐type microreactors is presented. Precise heat flux measurement is realized by means of Seebeck elements and allows for direct as well as space‐ and time‐resolved heat flux determination across the reactor. The microreactor used in this work is manufactured from poly(vinylidene fluoride) foils and consists of 11 SZ‐shaped mixing channel elements. The Seebeck elements are calibrated by the Joule effect, while its performance is demonstrated in heat transfer and neutralization reaction experiments. Furthermore, the local resolution enables an estimation of mixing time scale for rapid reactions. A comparison of obtained results indicates good accordance with literature data and is the base of further investigations using the calorimeter. Abstract : A Seebeck element‐based reaction calorimeter for measuring temporally and spatially resolved heat flux profiles across a continuously operated microreactor is proposed. With it, hot spots can be localized, thermokinetic data can be obtained, and mixing time scales can be derived from the heat flux profiles. At the same time, transparent material allows for optical observation of the chemical reaction.